Autobiografizm w twórczości Hanny Krall - Juchniewicz, Andrzej (Zagadnienia Rodzajów Literackich, 2024)
The article aims to prove that there are autobiographical threads in Hanna Krall’s reportages, which are related to the necessity to hide during the occupation, detention at the police station and the death of her mother. The discovery of autobiographical tropes in Krall’s work may change the reception of her publications. The first coded mentions of her life appear in Shielding the Flame. Still, commentators emphasized her influence on changing how the Warsaw Ghetto Uprising was told (Marek Edelman, the main witness of the uprising and its leader also contributed to this). So far, researchers have spotted autobiographical threads in the novel The Lodger, in which Krall’s occupation past becomes part of a plot based on fiction. An important clue that makes it possible to link Krall’s reportages with her biography is the interviews she gives. Reconstructing fragments of Krall’s biography can be considered a valuable source of information that has little to do with the need for self-creation and creating a specific image. Krall, as a child belonging to the “1.5” generation, left two variants of the records of her survival during the Holocaust. The first was in a small text entitled The Game for My Life. The second variant is her reportage books, where she allows for the emotions hidden in the text, thanking many people for their help. The author argues that the first variant contains a text for others, while the second is an attempt to convey the complicated feelings of a little girl who had to submit to the will of others.